PENGARUH DIMENSI AKSES DAN PENGGUNAAN KEUANGAN INKLUSIF TERHADAP PROFITABILITAS UNIT USAHA SYARIAH DI INDONESIA PERIODE 2017-2019 - Siti Mutmainnah; Uly Mabruroh Halida (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2021)
During the global financial crisis that occurred in 1998, the crisis in 2008, and the crisis in Europe in 2011, the European banking industry plummeted. However, several countries in Asia are experiencing growth. Asia's economic growth has not been supported by public access to financial institutions. Indonesian people's access to financial institutions is also still low due to the gap for the middle class who are not familiar with banking access (unbanked). To expand access to financial services, a financial inclusion program was launched. This study aims to determine the effect of the dimensions of access and use on financial inclusion on the profitability of Islamic Business Units in Indonesia for the 2017-2019 period, either partially or simultaneously. The research method uses quantitative research. This type of research uses associative. Data analysis used multiple linear regression analysis. The type of data in this study is secondary data. The object of this research is the Sharia Business Unit in Indonesia. The population in this study is the achievement of Islamic banking statistics published by OJK and population data published by BPS. Sampling in this study is to use a saturated sample. The results of this study indicate that the dimension of access to financial inclusion has no effect on profitability, it can be seen from the value of tcount -1.130 < ttable 2.03224. While the dimension of access to financial inclusion has a negative effect on profitability, it can be seen from the value of tcount -4.612 > ttable 2.03224,. Simultaneously, the dimensions of access and use of financial inclusion have an effect on profitability, it can be seen from the Fcount value of 32.486> Ftable 3.28.